LISTERIOSIS: OBSTETRIC AND PERINATAL ASPECTS - Onopchenko , Svitlana; Siusiuka , Volodymyr; Korniienko , Olena; Bohuslavska , Nataliya; Kyryliuk , Oleksandr; Shevchenko , Anna; Babinchuk , Olena (Collection of scientific papers «ΛΌГOΣ», 2024)
The article summarises the current data on listeriosis in pregnant women, taking into account the fact that the infection rate in this population is several times higher than in general population. Listeriosis in pregnant women is characterised by miscarriage, stillbirth, fever and flu-like symptoms. Therefore, listeriosis should be considered as a cause of fever in pregnancy in order to initiate appropriate treatment early. Prevention remains the best way to control listeriosis and should be reinforced, especially among patients and healthcare workers.